ARC Life Course Centre International Data for Policy Workshop - Francis Mitrou; Janeen Baxter; Mark Western; Ariel Kalil; Alison Park; Andrew Sporle; Barry Milne; Chris Orton; Rachel Christie; Carrie Samuels; Claire Sparke; Marcel Van Kints; et al. (International Journal of Population Data Science)
Objectives Identify factors that support development of socially acceptable next generation linked data ecosystems that deliver higher standards in research, evaluation, and evidence-based policy.